Low-salt diet downregulates plasma but not tissue kallikrein-kinin system - Hilgenfeldt, Ulrich; Puschner, Tanja; Riester, Udo; Schwarz-Finsterle, Jutta; Hilgenfeldt, Jürgen; Ritz, Eberhard (American journal of physiology. Renal physiology, 1998)
The kallikrein-kinin system (KKS) is involved in the regulation of blood pressure and in the sodium and water excretion. In humans, the KKS is divided functionally into a plasma KKS (pKKS) generating the biologically active peptide bradykinin and into the tissue (glandular) KKS (tKKS) generating the active peptide kallidin. The objective of this study was to examine the effect of a low-NaCl diet on the concentration of both pKKS and tKKS in plasma and urine in 10 healthy volunteers. After a 4-day low-NaCl diet, the urinary sodium and chloride excretions had decreased from 234 to 21.2 mmol/24 h and from 198 to 14.6 mmol/24 h, respectively. The plasma levels of ANG I, aldosterone, and angiotensin converting enzyme (ACE) significantly increased from 50.4 to 82.8 pg/ml, from 129 to 315 pg/ml, and from 46.4 to 59.8 U/ml, respectively, demonstrating the physiological adjustment to the low-salt diet. In plasma, the levels of bradykinin and plasma kallikrein had significantly decreased from 13.7 to 7.57 pg/ml and 14.4 to 7.13 U/ml, respectively. However, the levels of high-molecular-weight kininogen (HMW kininogen) remain unchanged (101 vs. 112 μg/ml, not significant). Contrary to plasma kallikrein, the plasma levels of tissue kallikrein increased (0.345 vs. 0.500 U/ml;P < 0.01). The plasma kallidin levels, however, did not change (64.7 vs. 68.6 pg/ml, not significant). This can be explained by a simultaneous decrease in the plasma low-molecular-weight kininogen (LMW kininogen) levels (89.9 vs. 44.4 μg/ml; P < 0.05). As in plasma, we find increased urinary concentrations of renal (tissue) kallikrein (23.3 to 42.8 U/24 h; P < 0.05) that contrast with, and are presumably counterbalanced by, urinary LMW kininogen levels (77.0 vs. 51.8 μg/24 h;P < 0.05). Consequently, in urine low-NaCl diet caused no significant change in either bradykinin or kallidin (9.2 vs. 10.8 μg/24 h, and 10.9 vs. 10.3 μg/24 h). It is concluded that the stimulation of the renin-angiotensin system on a low-NaCl diet is associated with a decrease in pKKS (bradykinin and plasma kallikrein) but not in tissue and renal KKS. Although tissue kallikrein is increased, there is no change in kallidin, as LMW kininogen in plasma and urine is decreased. These data suggest a difference in the regulation of pKKS and tKKS by low-salt diet.